A comprehensive parametric investigation of hemispherical cavities on thermal performance and flow-dynamics in the triangular-duct solar-assisted air-heater. (August 2021) - Goel, Varun; Kumar, Rajneesh; Bhattacharyya, Suvanjan; Tyagi, V.V.; Abusorrah, Abdullah M.
Abstract: The thermal energy available in the form of solar radiation is collected and converted into heat with the help of a solar air heater. The flow and thermal characteristics change significantly with the cross-sectional shape of the flow passage. The effect of hemispherical dimple-cavities that were employed over the heat-collector plate has been analyzed based on the flow and heat characteristics of a triangular solar air heater. A comprehensive investigation of roughness and flow parameters is carried out experimentally, while the flow dynamics over the heat-collector plate are predicted using commercial software (ANSYS). The remarkable results are observed in terms of Nusselt number and friction factor with the use of dimples over the heat-collector plate in the solar air heater. The higher heat transfer is noticed at the training edge in comparison to the leading edge of the dimple. The best augmentation in Nusselt number obtained is of the order of 5.33 that is observed for transverse-pitch ratio, longitudinal-pitch ratio and relative dimple depth values of 11, 11 and 0.039 respectively, at Reynolds number value of 2160. A close fit curve was obtained between the values obtained from the developed correlation and experimental values with a maximum error of 6.61% and 7.03%, respectively. Highlights: A new solar air heater with hemispherical dimples has been proposed. The best augmentation of heat obtained is 5.33 compared to Smooth SAH. 38.42% higher thermal performance obtained in proposed SAH over conventional. The best thermohydraulic performance parameter obtained is 3.48. A generalized expression developed for the Nusselt number and friction factor.